Perbedaan Tingkat Pemahaman Akuntansi Di Antara Mahasiswa Berdasarkan Kelulusan Pada Mahasiswa Semester II Tahun Angkatan 2017 Di Program Studi Akuntansi Universitas Muara Bungo - Riskawati, Eri (PT. Anagata Sembagi Education, 2024)
This study aims to investigate whether disparities exist in the comprehension of accounting concepts among students with diverse educational backgrounds. The research is conducted at the Faculty of Economics, Muara Bungo University, focusing on students majoring in Accounting. The study population comprises 62 second-semester students at Muara Bungo University (UMB). Quantitative descriptive data analysis, presented in the form of frequency tables, is employed for this research. The Likert scale is utilized as the scoring technique to evaluate respondents' answers to the questionnaire. According to the American Accounting Association, accounting is defined as the process of identifying, measuring, and reporting economic information to facilitate informed decision-making for stakeholders. The findings indicate significant discrepancies in the comprehension levels of assets among students from vocational schools specializing in accounting, high schools with a focus on social studies, and general Madrasah Aliyah. Similarly, there are noteworthy variations in the understanding levels of liabilities and equity among students from different educational backgrounds.